2016
DOI: 10.1007/s12011-016-0749-5
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory Cytokines Are Involved in Fluoride-Induced Cytotoxic Potential in HeLa Cells

Abstract: This study was designed to investigate the pro-inflammatory cytokines and their involvement in the cytotoxic potential of fluoride (F) in HeLa cells. HeLa cells were cultured with varying F concentrations (1-50 mg/L) for 48 h, and treatment effects were analyzed. The viability of HeLa cells was determined with a colorimetric method. The concentrations of IL-1β, IL-2, IL-6, and TNF-a in culture supernatant were measured through enzyme linked immunosorbent assay (ELISA). The mRNA expression levels of IL-1β, IL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…It has been reported that NaF can suppress the cellular immunity in mice and Th2 cytokines, including IL-4, IL-6, and IL-10, and Th17 cytokine (IL-17A) contents were decreased after exposed to NaF in excess of 12 mg/kg . In addition, our findings are consistent with some reports that high fluoride decreased the percentages of thymic CD4+ and CD8+T cells and IL-2 and IL-10 mRNA expression in mice, and at the cellular level, high NaF concentrations (20 and 50 mg/L) significantly reduced the secretion of TNF-α, IL-2, IL-6, and IL-1β in the supernatant . Therefore, we speculate that NaF affects the inflammation and immune response of rat heart tissue by affecting factors such as IL-6 and IL-10.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been reported that NaF can suppress the cellular immunity in mice and Th2 cytokines, including IL-4, IL-6, and IL-10, and Th17 cytokine (IL-17A) contents were decreased after exposed to NaF in excess of 12 mg/kg . In addition, our findings are consistent with some reports that high fluoride decreased the percentages of thymic CD4+ and CD8+T cells and IL-2 and IL-10 mRNA expression in mice, and at the cellular level, high NaF concentrations (20 and 50 mg/L) significantly reduced the secretion of TNF-α, IL-2, IL-6, and IL-1β in the supernatant . Therefore, we speculate that NaF affects the inflammation and immune response of rat heart tissue by affecting factors such as IL-6 and IL-10.…”
Section: Discussionsupporting
confidence: 91%
“…Elevated IL-6 level is related to cardiac hypertrophy, heart failure, and cardiac fibrosis . Related work indicates that NaF could down-regulate the levels of cytokines such as IL-2, IL-4, IL-6, IL-10, and TNF-α. After tissue damage, IL-6 and IL-1 can be rapidly produced to stimulate acute phase reactions, hematopoiesis, and immune responses, which contribute to host defenses, but continuous up-regulation can lead to pathological changes in chronic inflammation and autoimmunity. As an anti-inflammatory cytokine, IL-10 plays a protective role in the heart .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to fluoride has been shown to induce inflammatory responses in lung epithelial cells [ 39 ], HeLa cells [ 40 ], THP1 differentiated monocytes/macrophages [ 32 ], peritoneal macrophages [ 36 ], aorta [ 16 ], neuron [ 37 ] and testicle [ 20 , 21 ]. However, very limited reports are focused on fluoride-induced inflammatory responses in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study by Wang et al on HeLa cells showed a fluoride-induced stimulation of the synthesis of proinflammatory cytokines IL-1β, IL-2, IL-6, and TNF-α [87]. Activation of microglia in the hippocampus and cerebral cortex was also demonstrated in the rat model where fluoride, by influencing the production of these cytokines, contributed to the formation and progression of inflammation in the brain [88].…”
Section: Inflammation In Admentioning
confidence: 99%